From charity to change : inside the world of Canadian foundations - Pearson, Hilary M. (McGill-Queen's University Press, 2022)
"The world of philanthropy and private foundations remains mysterious to most Canadians. Memorably likened to giraffes, foundations are "creatures that should not exist, but they do, surrounded by a certain mystique." In From Charity to Change Hilary Pearson demystifies the world of Canadian philanthropy, offering a portrait of today's foundation landscape and highlighting organizations that are acting with purpose on some of the most pressing social and economic challenges of our time: climate change, the future of cities, education and the evolving workforce, housing, and the urgent need to repair and build new relationships with Indigenous Peoples. Pearson, who for two decades worked with leaders of foundations across Canada, provides an insider's perspective on the ways these organizations continue to evolve. Through personal interviews with private funders--large and small, long-established and newly-formed--Pearson describes their strategies and the varied roles they play, whether as convenors, advocates, brokers, or partners. A timely contribution to the current debate on the legitimacy of organized philanthropy in an era of increasing social division and inequality, From Charity to Change makes a compelling case for the valuable role private philanthropy plays in addressing the challenges of our rapidly changing times."--